2011
DOI: 10.1021/ie101907h
|View full text |Cite
|
Sign up to set email alerts
|

Modified Bounded Homotopies in the Solving of Phase Stability Problems for Liquid–Liquid Phase-Splitting Calculations

Abstract: In this study, the modified bounded homotopies presented by Malinen and Tanskanen (Malinen, I.; Tanskanen, J. Modified bounded homotopies to enable a narrow bounding zone. Chem. Eng. Sci. 2008, 63, 3419) are investigated in order to solve phase stability analysis problems in liquidÀliquid equilibrium cases for phase-splitting calculations. The tangent-plane distance criterion is used to analyze the phase stability. The emphasis is on approaching the first root on the homotopy path. According to the observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
8
0
1
Order By: Relevance
“…However, any method for the determination of phase stability could be integrated, including global optimization methods for the determination of the minimum of Gibbs free energy. Refer to the articles of Kangas et al and Zhang et al for a review of global optimization approaches for phase equilibrium calculation. Similar to the application in optimization-based process design, the main reason for the implementation of the homotopy continuation approach is its computational efficiency, which is an operational necessity for the multitude of evaluations required for the pinch branch calculations.…”
Section: Continuation-based Calculation Of Pinch Branches and Azeotropesmentioning
confidence: 99%
“…However, any method for the determination of phase stability could be integrated, including global optimization methods for the determination of the minimum of Gibbs free energy. Refer to the articles of Kangas et al and Zhang et al for a review of global optimization approaches for phase equilibrium calculation. Similar to the application in optimization-based process design, the main reason for the implementation of the homotopy continuation approach is its computational efficiency, which is an operational necessity for the multitude of evaluations required for the pinch branch calculations.…”
Section: Continuation-based Calculation Of Pinch Branches and Azeotropesmentioning
confidence: 99%
“…However, several authors have reported the failure of these criteria . As such, Kangas et al found that the fixed-point homotopy yields paths that converge to only certain solution vectors, which means that there are discontinuous homotopic paths in real domain. At this point, it is necessary to say that in other engineering fields Affine homotopy (Section 2.8.3) is placed in the same category of fixed-point homotopy .…”
Section: Homotopy Theorymentioning
confidence: 99%
“…Furthermore, the most novel approaches have been used in phase separation problems. Kangas et al used the bounded homotopy strategies of Malinen and Tanskanen to develop a robust method to calculate global minima. The general demeanor of the three classical homotopy forms was characterized based on their studies (Newton, FPN).…”
Section: Contemporary Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Una excelente revisión sobre la aplicación de los métodos de convergencia local y de optimización global a la solución numérica del problema del equilibrio de fases isotérmico-isobárico, puede encontrarse en el trabajo presentado por Wakeham y Stateva (2004). En la última década, sólo algunos estudios han sido enfocados al cálculo de los equilibrios líquidos multifásicos con modelos de energía de Gibbs de exceso, entre los cuales se encuentran los reportados por Stateva et al (2000), García-Sánchez et al (2001), Solokhin et al (2002), Guo et al (2004), Denes et al (2006), Marcilla et al (2009) y Kangas et al (2011. Estos autores utilizaron diferentes estrategias numéricas para encontrar la solución del problema del flash isotérmico-isobárico de sistemas ternarios y/o cuaternarios que presentan múltiples fases líquidas.…”
Section: Representación De Los Equilibrios Líquidos Multifásicosunclassified